Dampak Program Dana Bergulir Bagi Usaha Kecil dan Menengah (UKM) - Setiawan, Achma Hendra; Rejekiningsih, Tri Wahyu (Jurnal Ilmiah Aset, 2009)
The financial program to public sector was revolving fund by Department of Cooperation and Small and Medium Enterprises can be improving income’s public sectors and small and medium enterprises. Fragment, with revolving fund, small and medium enterprises can absorb labor force. So, revolving fund must be continuing for small and medium enterprises.By revolving fund, small and medium enterprises have to increase on employee (75%), capital (35.71%), economic scale (50%) and profit (50.27%). Coefficient of correlation 0.8819 is means that small and medium enterprises can be absorb of labor force. So, the revolving fund for small and medium enterprises was continuing and more than before. Fragment, to purpose employment and growing up of economy.